2020
DOI: 10.1177/1049731520972779
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Self-Compassion Writing Intervention for Adults With Mental Illness

Abstract: Purpose: Studies have found that writing with self-compassion about a stressful event helps promote mental health in college students and nonclinical populations. Using a randomized controlled trial, this study investigated whether a self-compassion writing intervention would lead to increases in self-compassion and proactive coping and reductions in mental health symptoms in a sample of individuals with mental illness. Method: Individuals with mental disorders were recruited and randomly assigned to a treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
7
0
3
Order By: Relevance
“…Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies administered interventions via a smartphone app (Al-Refae et al, 2021 ; Mak et al, 2018 ; Schnepper et al, 2020 ). Two studies involved self-compassion interventions that used self-help workbooks (Held & Owens, 2015 ; Sommers-Spijkerman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies administered interventions via a smartphone app (Al-Refae et al, 2021 ; Mak et al, 2018 ; Schnepper et al, 2020 ). Two studies involved self-compassion interventions that used self-help workbooks (Held & Owens, 2015 ; Sommers-Spijkerman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies involved female participants only (Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Kelman et al, 2018 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Navab et al, 2019 ; Noorbala et al, 2013 ; Savari et al, 2021 ; Seekis et al, 2020 ) while one study involved male participants only (Held & Owens, 2015 ). Of the 56 studies, 20 studies directly targeted people who reported psychological distress symptoms, such as depressive symptoms, anxiety, and stress (Anuwatgasem et al, 2020 ; Beshai et al, 2020 ; Bluth et al, 2016 ; Cândea & Szentágotai-Tătar, 2018 ; Collado‐Navarro et al, 2021 ; DeTore et al, 2022 ; Fernandes et al, 2022 ; Guo et al, 2020 ; Javidi et al, 2021 ; Kelly et al, 2009 ; Noorbala et al, 2013 ; Preuss et al, 2021 ; Savari et al, 2021 ; Schuling et al, 2020 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Torrijos‐Zarcero et al, 2021 ; Urken & LeCroy, 2021 ; Yadavaia et al, 2014 ). Two studies directly targeted individuals with low levels of self-compassion (Arimitsu, 2016 ; Yadavaia et al, 2014 ), and two studies directly targeted adults with high levels of self-criticism (Krieger et al, 2019 ; Shahar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, all three types of self-compassionate instruction, but none of the open-reflection instructions, were associated with increased selfcompassionate content of participants' expressive writing. To our knowledge, ours is the first study to demonstrate this effect over diverse types of self-compassionate instruction (e.g., Shapira & Mongrain, 2010;Urken & LeCroy, 2021). On this basis, we suggest that future interventions consider trialing "composite" versions of selfcompassion instructions that incorporate features of self-kindness, common humanity, and mindfulness (Dreisoerner et al, 2021).…”
Section: The Benefits Of Self-compassionate Expressive Writingmentioning
confidence: 67%
“… Robinson and Murphy-Nugen (2018) also showed the benefits of life review writing for older adults who are at risk of isolation and depression. Johnson and O’Brien (2013) and Urken and LeCroy (2021) also found that self-compassionate writing interventions led to improvements in self-compassion and mental health. Therefore, writing letters to one’s past-self appears to be a good method for people of various ages and with a wide range of mental health conditions.…”
Section: Discussionmentioning
confidence: 93%